2021
DOI: 10.1111/ijcs.12670
|View full text |Cite
|
Sign up to set email alerts
|

A consumer culture theory perspective of the marketplace: An integrative review and agenda for research

Abstract: In the last decades, the focus of studies on consumer behavior has changed from the individual to the group. Classical theories based on economic utility are insufficient to understand this phenomenon. Therefore, a new theoretical and postmodern approach seems necessary. Despite the increasing popularity of consumption communities, the investigation in the field is still dispersed. This study represents one first attempt to synthesize findings on the topic, in light of the consumer culture theory (CCT) traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 87 publications
(380 reference statements)
0
10
0
1
Order By: Relevance
“…Hungara and Nobre's (2021) review on consumer culture theory using 48 articles across 24 different journals explains the typology of consumption communities (e.g., small vs. large groups), concepts (e.g., assemblage thinking and consumption experiences) and theories (e.g., service dominant logic; social capital, exchange, network, and practice theories), as well as the antecedents (e.g., anti‐brand community participation; attachment or ownership to brands, products, and services; and hedonic and utilitarian community factors), mediators/moderators (e.g., community type and sociocultural issues), and consequences (e.g., ephemerality, identity co‐creation, and subcultural antagonism) often studied using consumer culture theory.…”
Section: Exemplars Of Systematic Literature Reviewsmentioning
confidence: 99%
“…Hungara and Nobre's (2021) review on consumer culture theory using 48 articles across 24 different journals explains the typology of consumption communities (e.g., small vs. large groups), concepts (e.g., assemblage thinking and consumption experiences) and theories (e.g., service dominant logic; social capital, exchange, network, and practice theories), as well as the antecedents (e.g., anti‐brand community participation; attachment or ownership to brands, products, and services; and hedonic and utilitarian community factors), mediators/moderators (e.g., community type and sociocultural issues), and consequences (e.g., ephemerality, identity co‐creation, and subcultural antagonism) often studied using consumer culture theory.…”
Section: Exemplars Of Systematic Literature Reviewsmentioning
confidence: 99%
“…Based on the size and strength of the articles' citations and/or occurrences, a bibliometric review well complements other literature reviews (Gupta & Dhingra, 2022;Halder et al, 2021;Paul & Criado, 2020;Rawat et al, 2022) in showing a topic's origin, evolution, influence, and advancements at a macro level (Chakma et al, 2021). Following the SPAR-4-SLR protocol of , we conduct a comprehensive and conceptual (Rawat et al, 2022) hybrid review (Paul & Criado, 2020) by integrating bibliometric review and systematic literature review, as adopted by earlier business management researchers (Chakma et al, 2021;Das et al, 2022;Harju, 2022;Hungara & Nobre, 2021;Paul & Bhukya, 2021) (Figure 1). SPAR-4-SLR, which has been designed to conduct systematic literature reviews specifically (Paul et al, 2021, p. 6), provides a rationale, topical, consistent, transparent, and robust protocol (Harju, 2022;Khatri & Duggal, 2022;Lim et al, 2022;Rawat et al, 2022) to assemble, arrange, and assess vast literature in a systematic and exhaustive way (Gupta & Dhingra, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the size and strength of the articles' citations and/or occurrences, a bibliometric review well complements other literature reviews (Gupta & Dhingra, 2022; Halder et al, 2021; Paul & Criado, 2020; Rawat et al, 2022) in showing a topic's origin, evolution, influence, and advancements at a macro level (Chakma et al, 2021). Following the SPAR‐4‐SLR protocol of Paul et al (2021), we conduct a comprehensive and conceptual (Rawat et al, 2022) hybrid review (Paul & Criado, 2020) by integrating bibliometric review and systematic literature review, as adopted by earlier business management researchers (Chakma et al, 2021; Das et al, 2022; Harju, 2022; Hungara & Nobre, 2021; Paul & Bhukya, 2021) (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, consumer culture frames consumers' feelings, thoughts, and emotions to form certain behavioral tendencies and patterns that are divergent from other people [23,32]. Although CCT, as a collection of theoretical perspectives rather than an ultimate theory, does not directly establish nomothetic models, it facilitates researchers and practitioners comprehending the complex and dynamic relationship among cultural values, consumer behaviors and the marketplace [30,34]. Based on prior research, ethnocentrism and cosmopolitanism are identified as critical consumer values determining consumers' decision-making process and consumption behaviors [4,5,7,35].…”
Section: Theoretical Underpinning To Purchase Intentionsmentioning
confidence: 99%